A Structural Approach to Assessing Innovation: Construct Development of Innovation Locus, Type, and Characteristics - Gatignon, Hubert; Tushman, Michael L.; Smith, Wendy; Anderson, Philip (Management Science, 2002)
We take a structural approach to assessing innovation. We develop a comprehensive set of measures to assess an innovation's locus, type, and characteristics. We find that the concepts of competence destroying and competence enhancing are composed of two distinct constructs that, although correlated, separately characterize an innovation: new competence acquisition and competence enhancement/destruction. We develop scales to measure these constructs and show that new competence acquisition and competence enhancing/destroying are different from other innovation characteristics including core/peripheral and incremental/radical, as well as architectural and generational innovation types. We show that innovations can be evaluated distinctively on these various dimensions with generally small correlations between them. We estimate the impact these different innovation characteristics and types have on time to introduction and perceived commercial success. Our results indicate the importance of taking a structural approach to describing innovations and to the differential importance of innovation locus, type, and characteristics on innovation outcomes. Our results also raise intriguing questions regarding the locus of competence acquisition (internal vs. external) and both innovation outcomes.